Co-digestion of Oil Palm Trunk Hydrolysate and Slaughterhouse Wastewater for Biohydrogen Production in a Fixed Bed Reactor by Immobilized Thermoanaerobacterium thermosaccharolyticum KKU19 on Expanded Clay - Khamtib, Sontaya; Sittijunda, Sureewan; Imai, Tsuyoshi; Reungsang, Alissara (Frontiers in Energy Research, 2021)
The goal of this study was to evaluate the use of expanded clay as a support material for Thermoanaerobacterium thermosaccharolyticum KKU19 to produce hydrogen from oil palm trunk hydrolysate (OPT) and slaughterhouse wastewater (SHW) in a fixed-bed reactor (FBR) under non-sterile conditions. The effects of hydraulic retention time (HRT) on the performance of the FBR were also investigated. The FBR was operated at an OPT hydrolysate to SHW ratio of 2.55:1 (v:v), 60C, initial pH 6.5, and 1.2 mg (as total volatile solids/g expanded clay) of T. thermosaccharolyticum KKU19 immobilized on expanded clay. A maximum hydrogen production rate (HPR) and hydrogen yield (HY) of 7.15 ± 0.22 L/L d and 234.45 ± 5.14 L H2/L d, respectively, were obtained at an HRT of 6 h. Long-term operation of FBR at 6 h HRT indicated that expanded clay efficiently immobilizes T. thermosaccharolyticum KKU19, for which an HPR of 6.82 ± 0.56 L H2/L d, and an HY of 231.99 ± 19.59 mL H2/g-COD were obtained. Furthermore, the COD removal efficiency of 30% obtained under long-term operation was comparable to that under short-term operation at an HRT of 6 d. Butyric and acetic acids were the main soluble metabolite products, thereby indicating a butyrate–acetate type fermentation. Our findings indicate that expanded clay is an effective support material that contributes to the protection of microbial cells and can be used for long-term operation.